Analysis of the Coupling Effect of Thermal and Traffic Loads on Cement Concrete Pavement with Voids Repaired with Polymer Grout. (13th January 2022) - Cui, Can; Lu, Qing; Guo, Chengchao; Wang, Fuming
Abstract : Under the repeated action of traffic and thermal loads, a cement concrete pavement slab may partially lose contact with its base course, and voids may develop underneath the slab. Such distress will greatly impact the pavement performance. To fill the voids and restore the base support to the slab, the technology of polymer grouting has been increasingly adopted in recent years due to its advantages of quick application and high efficiency. There is, however, a lack of research on the mechanistic responses and performance of such a repaired rigid pavement under coupled influences of thermal and traffic loads. Existing literature has mainly focused on normal cement concrete pavement structures (i.e., without polymer grouted voids). This study intends to fill the research gap by investigating the time-domain characteristics of thermal stress response of a cement concrete pavement with underlying voids filled with polymer grout, along with design traffic loads. The finite element method was adopted with a 3-dimensional nonlinear temperature field within the pavement. A program module was developed in the Abaqus FEA software environment for temperature effect analysis. It was found that under the coupling action of thermal and traffic loads, thermal stress had a greater influence on the critical slab stress at the slab corner than those at other slab locations. Through the comparative analysis before and after polymer grouting repair, the critical tensile stress at the slab corner under the vehicle and thermal loads can be effectively reduced. The polymer performance is stable after three years.